Karakteristik Karakteristik Komite Audit Terhadap Kecurangan Pelaporan Keuangan (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Sambo, Eva Marin; Sufiati; Sunbanu, Andika (Insan Cita Bongaya Research Journal, 2024)
This study aims to determine the effect of the characteristics of the audit committee, namely the independence of the audit committee, the financial expertise of the audit committee and the frequency of audit committee meetings on fraudulent financial reporting in banking companies listed on the Indonesia Stock Exchange especially during the Covid-19 pandemic. This study uses secondary data obtained from the financial statements of companies in the banking sub-sector for the 2019-2021 period in accordance with the COVID-19 pandemic using the purposive sampling method. The population in this study are banking companies listed on the Stock Exchange, the sample taken is 29 banking companies for a 3-year research period, the research sample is 87 samples. The results of the study have been tested for classical assumptions in the form of normality test assumptions. The data analysis method used logistic regression. Based on the results of the criteria obtained, there are 87 companies selected as samples, consisting of 45 non-fraud companies and 42 fraudulent companies. The results showed that the audit committee's independence variable was not significant to financial reporting fraud, while the audit committee's financial expertise and audit committee meeting frequency had a significant negative effect on financial reporting fraud during the covid-19 pandemic in banking companies listed on the Indonesia Stock Exchange.